Aldatıcı reklamlara karşı tüketicinin korunması - İçöz, Derya (My University, 2008)
ALDATICI REKLAMLARA KARŞI TÜKETİCİNİN KORUNMASI Ülke ekonomisinde önemli bir yere sahip olan ve sayısız misyonu içinde barındıran reklamlar, birçok açıdan oldukça önem ve çeşitliliğe sahiptir. Bu çalışmada reklamlar, özellikle Tüketici mevzuatı çerçevesinde incelenerek tüketici perspektifinden reklamların aldatıcı nitelik taşıyıp taşımadığı değerlendirilmiştir. Bu çerçevede reklam tanım ve unsurları, reklamın hukuki niteliği, aldatıcı reklam tanım ve unsurları, aldatıcı reklam teşkil eden başlıca haller, aldatıcı reklamlara karşı sorumlu kişiler ve aldatıcı reklamlara karşı tüketicinin korunmasına ilişkin hukuki düzenlemeler incelenmiştir. Aldatıcı reklamlara karşı başvurulabilecek, Özdenetim, Reklam Kurulu, Radyo Televizyon Üst Kurulu, Tüketicinin Korunması Hakkında Kanun’un ayıp, Borçlar Kanunu’nun hile ve ayıp ve TTK’nın haksız rekabet hükümleri değerlendirilmiştir. Neticede aldatıcı reklamların özellikle tüketicinin korunması bakımından üzerinde geniş inceleme ve çalışmalar gerektirecek nitelikte öneme sahip olduğu tespit edilmiştir.

PROTECTION OF CONSUMERS AGAINST DECEPTIVE ADVERTISEMENTS Advertisements that play a great role in the national economy and that contain countless of missions are considerably important and have a great variety in many aspects. In this study, advertisements are examined in particular in accordance with regulations concerning Consumers, and it is assessed whether advertisements have a deceptive nature from the perspective of consumers. In this context, legal arrangements are examined, which are relating to definition and components of the advertisement, legal nature of the advertisement, definition and components of the deceptive advertisement, principal situations that establish deceptive advertisements, persons who are responsible for deceptive advertisements, and protection of consumers against deceptive advertisement. The followings that may be appealed to against deceptive advertisements are assessed; Self-Policing, the Board of Advertisement, the Radio and Television Supreme Council, the provisions of the Law concerning Protection of Consumers, the Code of Obligations, and Turkish Commercial Code in respect of defects, deceptions and defects, and unfair competition respectively. Consequently, it is determined that the subject of deceptive advertisements have such an importance that require a large analysis and studies in particular in respect of protection of consumers.
Keywords: Hukuk; Özel Hukuk; Reklamlar_Hukuk; Tüketici Hakları